Estimating the Effectiveness of DPYD Genotyping in Italian Individuals Suffering from Cancer Based on the Cost of Chemotherapy-Induced Toxicity - Fragoulakis, Vasileios; Roncato, Rossana; Fratte, Chiara Dalle; Ecca, Fabrizio; Bartsakoulia, Marina; Innocenti, Federico; Toffoli, Giuseppe; Cecchin, Erika; Patrinos, George P; Mitropoulou, Christina (American journal of human genetics, 2019)
Fluoropyrimidines (FLs) have been widely used for more than 60 years against a range of solid tumors and still remains the cornerstone for the treatment of colorectal, gastric, and breast cancer. Here, we performed an economic analysis to estimate the cost of DPYD-guided toxicity management and the clinical benefit expressed as quality adjusted life years (QALYs) in a large group of 571 individuals of Italian origin suffering from cancer and treated with a fluoropyrimidines-based chemotherapy. Individuals suffering from cancer with a histologically confirmed diagnosis of cancer, who received a fluoropyrimidines-based treatment, were retrospectively genotyped in the DPYD gene. Effectiveness was measured as survival of individuals from chemotherapy, while study data on safety and efficacy as well as on resource utilization associated with each adverse drug reaction were used to measure costs to treat these adverse drug reactions. A generalized linear regression model was used to estimate cost differences for both study groups. DPYD extensive metabolizers (528 individuals) had greater effectiveness and lesser cost, representing a cost-saving option over DPYD intermediate and poor metabolizers (43 individuals) with mean QALYs of 4.18 (95%CI: 3.16-5.55) versus 3.02 (95%CI: 1.94-4.25), respectively. Our economic analysis showed that there are some indications for differences in survival between the two groups (p > 0.05), while the cost of DPYD extensive metabolizers was significantly lower (p < 0.01) compared with those belonging to the group of intermediate/poor metabolizers. These findings suggest that DPYD-guided fluoropyrimidines treatment represent a cost-saving choice for individuals suffering from cancer in the Italian healthcare setting.